2011
DOI: 10.1007/s00221-011-2652-9
|View full text |Cite
|
Sign up to set email alerts
|

Differing roles for the dominant and non-dominant hands in the hand laterality task

Abstract: Determining the handedness of visually presented stimuli is thought to involve two separate stages--a rapid, implicit recognition of laterality followed by a confirmatory mental rotation of the matching hand. In two studies, we explore the role of the dominant and non-dominant hands in this process. In Experiment 1, participants judged stimulus laterality with either their left or right hand held behind their back or with both hands resting in the lap. The variation in reactions times across these conditions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 21 publications
8
51
2
Order By: Relevance
“…The present work reported shorter RT for left hands, as opposed to some previous studies that reported an advantage in right hand recognition (Gentilucci et al, 1998b; Ionta and Blanke, 2009; Takeda et al, 2010; Ní Choisdealbha et al, 2011). A previous work has however reported that RT for left hands were shorter when participants responded with the right hand (Cocksworth and Punt, 2013).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The present work reported shorter RT for left hands, as opposed to some previous studies that reported an advantage in right hand recognition (Gentilucci et al, 1998b; Ionta and Blanke, 2009; Takeda et al, 2010; Ní Choisdealbha et al, 2011). A previous work has however reported that RT for left hands were shorter when participants responded with the right hand (Cocksworth and Punt, 2013).…”
Section: Discussioncontrasting
confidence: 91%
“…As a matter of fact, whatever the task, RH respond faster with their dominant hand while response times are less affected by the side of the response hand in LH (Rabbitt, 1978; Tzourio-Mazoyer et al, 2015). Two previous studies overcame this problem by including a response with the ipsilateral foot (Ní Choisdealbha et al, 2011) or an oral response (Ionta and Blanke, 2009). These works also reported faster responses for right hands in RH while LH exhibited no difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How this applies to interpreting action based on other people’s movements that are typically in the third person perspective is still unclear. Mentally simulated actions from an egocentric perspective are considered visually and motorically familiar (Ni Choisdealbha et al, 2011; Conson et al, 2012) as this affords optimization of motor imagery and action encoding. Alternatively, the allocentric perspective may not be motorically familiar to oneself, and in order to process allocentric action, motor imagery may necessitate visual transformations.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we adopted a paradigm, i.e. body posture manipulation, which has been widely used in motor imagery literature to demonstrate that mental imagery of actions strongly relies on information currently available from one's own body (Conson et al 2016;de Lange et al 2006;Funk et al 2005;Ni Choisdealbha et al 2011). Several studies demonstrated that body posture manipulation (i.e.…”
Section: Methodsmentioning
confidence: 99%